THE EFFECT OF LEVERAGE ON HEDGING THROUGH PROFITABILITY MEDIATION VARIABLES IN COMPANIES LISTED IN JAKARTA ISLAMIC INDEX (JII) IN 2015-2020 - Chandra Satria; Doly Nofiansyah; M Fazal Rizvi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This research is to analyze the effect of leverage on hedging with profitability as a mediating variable in companies listed on the Jakarta Islamic Index (JII) in 2015-2020. This research methodology uses quantitative methods with instrument testing using SEM Pls using SmartPLS software. The results show that Leverage has a significant positive effect on Profitability, Leverage has no effect on Hedging, Profitability has a significant positive effect on Hedging, Leverage has an effect on Hedging through Profitability. The limitation in the research is only the object in this study is still limited to companies listed on the Jakarta Islamic Index (JII). The research period carried out in this study was only 5 years, namely in 2015-2020, it is hoped that further research can use a longer period so that the level of research accuracy is higher and can add a variable level of currency prices to see the wider influence of leverage on the hedging of a company when viewed from investors who come from outside